(untitled) (Mustansiria Dental Journal, 2018)
This in vitro study was conducted to asses the affect of salivary contamination in case of air dried or not dried (kept moist) before the application of the bonding agent (prime and bond NT) on the microleakage of Dyract AP compomers (advance performance) in primary molars at the occlusal wall of class V preparations and compare it to the standardized technique of application. Sixty class V cavities were prepared in 30 teeth (exfoliated primary molars), the cavities were prepared in the middle third of the buccal and lingual surface of each crown and randomly divided into three groups (each group consists of 20 cavities) Group (I): air-dried after salivary contamination, Group (II): not dried after salivary contamination (kept moist), Group (III): with out salivary contamination. After the teeth were filled, stored in distilled water for 24 hours, thermocycled, stained with basic fuchsin dye, sectioned to record the extend of dye penetration under stereomicroscope. Results revealed that there is no difference in the linear microleakage among groups at the occlusl wall. Although the differences were not statistically significant, greater microleakage was found in group (I) indicating that if salivary contamination occur, it is better to leave the preparation moist rather than complete air dryness.